KARAKTER NORMATIF ISI NASKAH AKADEMIK UNDANG-UNDANG - Giri, Ni Putu Niti Suari (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 3 No 1 (2014), 2014)
The Article 43(3) Act Number 12, 2011 concerning Regulations Making stipulatedthat the act draft from DPR,  President, or DPD must be accompanied the academic text. However the function was from the obligation enclosed by thesubmitting the academic text still not well understood, so as the academic text was still being considered unimportant and ignored in the submitting act draft. Starting fromthese problems , then the problem that emerged that is what is the normative character of the contents of the academic text according to the law and the doctrine of legal knowledge. The purposeis tounderstand thecharacter ofthe normativecontent of the academic text according to the law and the doctrine of legal knowledge. The research that used was the juridical  normativeresearch. The legal source took form the regulations, literatures, results of the researches, papers in the seminar, the journals, articles, and reading materials that were linked with the problem that was studied in this research, the dictionaries and the legal encyclopedias. The use ofthe word' shall' in the regulations, that wordsis usedforthe fulfillment ofa conditionorspecific requirements. If the obligation that was arranged this was not fulfilled, that was relevant did not receive something or the matter that necessarily will be got if the condition or this condition was fulfilled. So the regulation to the Article 43 (3) was valid. The characteristics from the regulation concerning the obligation enclosed the academic text in putting forward the act draft  was to be imperative. The word'shall' bind the DPR, President and DPD to submitting  the academic text. If the academic text was not submitted, then the consequences that the act draftcould not be processed to the further stage.
Keywords: academic texts; normativecharacter; valid